PROBLEMS OF ORGANIZING THE WORK OF VISITING TEAMS OF MEDICAL SPECIALISTS - Казакова, Ольга Станиславовна; Лаптев, Евгений Владимирович; Московская, Елена Викторовна; Горяинова, Татьяна Николаевна; Мозес, Вадим Гельевич; Мозес, Кира Борисовна; Елгина, Светлана Ивановна; Рудаева, Елена Владимировна; Карелина, Ольга Борисовна (Medicine in Kuzbass, 2021)
The work analyzes the work of visiting teams of doctors of specialists of Kuzbass Regional Clinical Hospital named after S.V. Belyaev. The results of the study show that the planning of fieldwork is accompanied by errors at the planning stage. All this makes it necessary to search for and create a more effective mechanism for preliminary triage and selection of patients sent by the receiving party for an on-site consultation.